Long‐term changes in flowering synchrony reflect climatic changes across an elevational gradient. Issue 2 (20th January 2022) - Fisogni, Alessandro; de Manincor, Natasha; Bertelsen, C. David; Rafferty, Nicole E.
Abstract : Synchrony defines an organism's overlap with potential resources and mates, essential for survival and reproduction. Flowering synchrony influences gene flow within species and patterns of interaction among plants and with other trophic levels, including pollinators. Climate‐change driven shifts in plant phenology may disrupt plant–plant and plant–pollinator interactions, resulting in reshuffling of communities and altered ecosystem processes. We present a unique long‐term metacommunity‐wide study relating changes in flowering synchrony within and among species along an elevational gradient to changes in local climatic conditions. We apply a circular statistical method that estimates flowering phenology overlap between entire flowering distributions, overcoming limitations and biases of single indicators such as first and last flowering dates. We analyzed more than 300 000 flowering overlap estimates between 217 species in five plant communities across a 1267 m gradient over four decades (1984–2019) in the southwestern USA. We show that co‐flowering synchrony significantly decreased in all plant communities, with a maximum of 28.1% of synchrony lost at the lowest elevations. Decreased synchrony was significantly negatively correlated with increasing temperatures recorded across the gradient. Reduced precipitation had locally‐dependent effects and, in combination with warmer temperatures, accelerated the decrease in synchrony, especially at the lowest elevations. Flowering synchrony within plant species occurring in multiple communities increased between most community pairs, with a maximum increase of 30.5%, and at accelerated rates in recent years. The exception, likely associated with differences in topography, was a 5.6% decrease in synchrony between the two highest‐elevation communities. Overall, increased synchrony within species occurring at multiple elevations indicates homogenization of flowering phenology across the gradient. These results show significant reshaping of flowering synchrony within and between plant communities in response to changing climate. Because plant phenology influences many ecological processes, such fundamental changes may have far‐reaching and negative effects on ecosystem stability.